Deep dish - Andrews, Mary Kay (New York : Harper, 2008)
The Cooking Channel is looking for its next big star, and Gina is certain that she fits the bill. Trouble is, the execs also have their eyes on Mr. "Kill It and Grill It" Tate Moody, the star of a hunting, fishing, and cooking show named Vittles. Tate is the ultimate man's man, with a dog named Moonpie and a penchant for flannel shirts. He's also a tasty side of beef with a swooning female fan base. All Gina has on her side are a free-spirited, college-dropout sister and a mother who calls every single day. Little does Gina know, though, that she and Tate are soon to embark on the cook-off of their lives, spiced up by a little ingredient called love.--From publisher description.
Keywords: Women cooks; Cooking; Television